Controlled Intersystem Link Based on a "Hexagon" Scheme Converter - Kalinin L.P.; Zaitsev D.A.; Tirsu M.S.; Golub I.V.; Kaloshin D.N. (Problems of the Regional Energetics)
The aim of the paper is to research possibility to use a "hexagon" scheme static frequency converter as controlled intersystem link for two parallel operating power systems with different operating frequencies, or standards for frequency stabilization. The paper aims to study the transformer device operating characteristics that implements the output voltage phase circular rotation principle relative to the input voltage and controlled by power electronics. This goal is achieved through the elaborated "rough" device control strategy, which made it possible to provide controlled AC intersystem link of asynchronous power systems without the use of additional harmonic filters and dampers. Two sectioning modes of adjusting windings were used to apply 24 and 48 position laws of the converter "fine" control. The most significant results are the new technical solution of the frequency converter, as well as the "rough" control strategy. To assess the conversion quality, indicators were used that characterize the degree of stability of the transmitted power and the harmonic distortion of the current. The computational experiments results have shown the effectiveness of the proposed "rough" control strategy. It is proved that 48-position sectioning of the "fine" regulation winding can significantly improve the quality of conversion compare to 24-position. The obtained results significance is that developed technical solution provides acceptable indicators of the frequency conversion quality and transmitted active power stability. In addition, the use of the proposed converter technical solution can significantly reduce the number of windings and control means compare to previously ones studied by the authors.